2016
DOI: 10.1037/hea0000294
|View full text |Cite
|
Sign up to set email alerts
|

Anticipated regret and health behavior: A meta-analysis.

Abstract: Objective Risk beliefs are central to most theories of health behavior, yet many unanswered questions remain about an increasingly studied risk construct, anticipated regret. We sought to better understand anticipated regret’s role in motivating health behaviors. Methods We systematically searched electronic databases for studies of anticipated regret and behavioral intentions or health behavior. We used random effects meta-analysis to synthesize effect sizes from 81 studies (n=45,618). Results Anticipated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
157
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(176 citation statements)
references
References 62 publications
17
157
0
2
Order By: Relevance
“…These findings potentially speak to the idea that “losses loom larger than gains” — e.g., the potential to feel regret for not doing something that is healthful is more powerful than the potential to feel proud after doing something that is healthful, consistent with research on affective forecasting biases (e.g., “impact bias;” Ellis et al, 2018). The contribution observed by anticipated (inaction) regret in the present study is in line with the results of a recently published meta-analysis regarding the relationships between anticipated action and inaction regret and health behavior engagement (Brewer et al, 2016); however, notably, Brewer and colleagues did not explore the role of anticipated pride.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings potentially speak to the idea that “losses loom larger than gains” — e.g., the potential to feel regret for not doing something that is healthful is more powerful than the potential to feel proud after doing something that is healthful, consistent with research on affective forecasting biases (e.g., “impact bias;” Ellis et al, 2018). The contribution observed by anticipated (inaction) regret in the present study is in line with the results of a recently published meta-analysis regarding the relationships between anticipated action and inaction regret and health behavior engagement (Brewer et al, 2016); however, notably, Brewer and colleagues did not explore the role of anticipated pride.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, a growing literature has examined whether affective constructs, such as affective attitudes and anticipated affective reactions, ought to be explicitly incorporated into these traditionally cognitive-based models (Conner, McEachan, Taylor, O’Hara, & Lawton, 2015; Linde, Rhodes, Riley, & Spruijt-Metz, 2016; Rhodes & Nigg, 2011; Rivis, Sheeran, & Armitage, 2009; Sandberg & Conner, 2008; Sniehotta, Presseau, & Araújo-Soares, 2014; Williams, Rhodes, & Conner, 2017). While numerous studies have demonstrated the predictive utility of affective attitudes and negatively valanced anticipated affective reactions (i.e., anticipated regret; Brewer, DeFrank, & Gilkey, 2016; Ellis et al, 2018; Koch, 2014; Rivis et al, 2009; Sandberg & Conner, 2008; Sandberg, Hutter, Richetin, & Conner, 2016), the potential contribution of positively valanced anticipated affective reactions (e.g., pride) has received far less attention (Conner, Godin, Sheeran, & Germain, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22,40 A recent meta-analysis demonstrated that anticipated regret can be particularly effective in motivating health behaviors when highlighting the proximal and severe consequences of inaction. 41 Although consequences of HPV infection (e.g., cancer) may not be proximal, they can be quite severe. In addition to anticipated regret, both parents' and sons' willingness was associated with greater perceived importance of protecting the son's future partner from HPV-related illness.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 63 full-text articles were included in the review. Such a ratio of studies identified initially and eligible for inclusion in a review is common [123,124] . The study characteristics are presented in Table 1 .…”
Section: Results Of the Literature Searchmentioning
confidence: 99%